An uncanny case of paraneoplastic calcitriol mediated hypercalcaemia - Preet Mukesh Shah; Saadia Saeed; Susana Gonzalez (Endocrinology, Diabetes & Metabolism Case Reports, 2023)
A 77-year-old female patient with a history of treated breast cancer and a recently diagnosed laryngeal cancer presented with severe hypercalcaemia associated with suppressed parathyroid hormone (PTH) levels. Her initial investigations included 25-hydroxy vitamin D levels, short synacthen test, bone scan, myeloma screen and thyroid function tests which were within normality. A computerised tomography (CT) scan showed some right lung apical fibrotic changes. Her PTH-related peptide (PTHrP) was normal and sarcoidosis was also excluded. Her previous and current malignancies were thought to be unlikely behind her hypercalcaemia. Her 1,25-dihydroxy vitamin D (calcitriol) levels were found to be elevated. Her hypercalcaemia was initially managed with intravenous fluids and intermittent bisphosphonates infusions which would transiently reduce her calcium levels. Steroid treatment was initiated which improved her hypercalcaemia; however, the calcium levels rebounded on tapering the steroids down, a pre-requisite prior to a positron emission computerised tomography (PET-CT) scan to determine the source of the excess calcitriol production. This was cancelled following an emergency admission with marked hypercalcaemia and acute renal and liver injury. A contemporary CT scan showed a right apical lung mass with hepatic lesions suggestive of a disseminated lung primary. The histology obtained from a liver biopsy was compatible with metastatic small-cell lung carcinoma. Unfortunately, her clinical condition deteriorated further and she did not survive. To the best of our knowledge, this is the first report in the literature describing calcitriol-mediated hypercalcaemia due to a small-cell lung cancer.